2012
DOI: 10.1152/ajpendo.00245.2012
|View full text |Cite
|
Sign up to set email alerts
|

GLP-2 receptor in POMC neurons suppresses feeding behavior and gastric motility

Abstract: receptor in POMC neurons suppresses feeding behavior and gastric motility. Am J Physiol Endocrinol Metab 303: E853-E864, 2012. First published July 24, 2012; doi:10.1152/ajpendo.00245.2012.-Glucagon-like peptides (GLP-1/2) are cosecreted from endocrine L cells in the gut and preproglucagonergic neurons in the brain. Peripheral GLP-2 action is essential for maintaining intestinal homeostasis, improving absorption efficiency and blood flow, promoting immune defense, and producing efficacy in treatment of gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 55 publications
5
68
0
Order By: Relevance
“…In addition, knockout mice with GLP2R deletion selectively in hypothalamic arcuate nucleus neurons expressing proopiomelanocortin (POMC) display hyperphagic behaviour and late-onset obesity (Guan et al 2012). These observations support the hypothesis of a physiological role in the regulation of food intake and body weight (Guan et al 2012). Up to date, studies in humans have not demonstrated a decrease in food intake after peripheral GLP2 administration (Schmidt et al 2000, Sørensen et al 2003, even if recent data have shown that intraperitoneal injections of GLP2 or [Gly 2 ]-GLP2 reduce food intake in mice, suggesting a role for GLP2 in the short-term regulation of the eating behaviour (Baldassano et al 2012).…”
Section: Overview On Glp2mentioning
confidence: 77%
See 2 more Smart Citations
“…In addition, knockout mice with GLP2R deletion selectively in hypothalamic arcuate nucleus neurons expressing proopiomelanocortin (POMC) display hyperphagic behaviour and late-onset obesity (Guan et al 2012). These observations support the hypothesis of a physiological role in the regulation of food intake and body weight (Guan et al 2012). Up to date, studies in humans have not demonstrated a decrease in food intake after peripheral GLP2 administration (Schmidt et al 2000, Sørensen et al 2003, even if recent data have shown that intraperitoneal injections of GLP2 or [Gly 2 ]-GLP2 reduce food intake in mice, suggesting a role for GLP2 in the short-term regulation of the eating behaviour (Baldassano et al 2012).…”
Section: Overview On Glp2mentioning
confidence: 77%
“…In fact, intracerebroventricular administrations of GLP2 reduce food intake in rodents (Tang-Christensen et al 2000, Lovshin et al 2001. In addition, knockout mice with GLP2R deletion selectively in hypothalamic arcuate nucleus neurons expressing proopiomelanocortin (POMC) display hyperphagic behaviour and late-onset obesity (Guan et al 2012). These observations support the hypothesis of a physiological role in the regulation of food intake and body weight (Guan et al 2012).…”
Section: Overview On Glp2mentioning
confidence: 84%
See 1 more Smart Citation
“…MC4R has been associated with key components of nutrient absorption, lipid metabolism, energy expenditure, thermogenesis, adiposity, insulin secretion, food intake, and appetite (Adan et al 2006). Moreover, the MC pathway interacts with other key hormones or pathways such as leptin, 5-HT (Zhou et al 2007), NPY, AGRP, POMC (Biebermann et al 2012), and ANS (Rossi et al 2011;Sohn et al 2013) in the hypothalamus and brainstem (Loos 2011), GLP-1 pathway (Gautron et al 2010), CCK, and vagal afferent fibers (Guan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Future experiments should thus use loss-offunction strategies that are either inducible and/or involve more than one signaling pathway. For example, because GLP-2 has been demonstrated to act in addition to GLP-1 on appetite in the brain 56 and the two hormones may substitute for each other, a double GLP-1R/GLP-2R knockout strategy may be necessary. This line of reasoning is supported by studies using octreotide, a nonspecific inhibitor of all gut hormones.…”
Section: Potential Underlying Mechanisms For Change In Set Pointmentioning
confidence: 99%